Targeting entry into mitochondria for increased anticancer efficacy of BCL-XL-selective inhibitors in lung cancer. (March 2022) - Li, Liangping; Li, Pingping; Song, Huanhuan; Ma, Xuesong; Zeng, Shulan; Peng, Yan; Zhang, Guohai
Abstract: The BCL-XL -selective inhibitors exhibit potential clinical application value when combined with chemotherapeutic drugs for the treatment of solid tumors. However, their efficacy in these settings is still low when treated with BCL-XL inhibitors alone in solid tumors. The mechanism responsible for the poor efficacy remains unclear. We show here that unable to interact with target of BCL-XL -selective inhibitors caused by invalid entry into mitochondria is essential for their inefficacy in solid tumors. We demonstrated in non-small-cell lung cancer (NSCLC) cells that the instability of A-1155463 in cells as well as invalid entry into mitochondria of A-1331852, two BCL-XL -selective inhibitors, accounted for their off-target problems. Furthermore, we found that a mitochondria-targeted, non-toxic small molecule NA-2a improved the on-target effect of A-1331852 to enhance its apoptotic regulatory activity, thereby increasing its anticancer activity in NSCLC. Our results indicated that NA-2a was selectively enriched in mitochondria transported by organic-anion-transporting polypeptide (OATP) transporters, which altered the permeability of the mitochondrial membrane, thereby promoting the entrance of A-1331852 to mitochondria and enhancing its disruption of the BIM-BCL-XL complex, which finally led to the increased anticancer activity in vitro and in vivo. Collectively, our data provided overwhelming evidence that the combination of NA-2a and A-1331852 could be used as a promising synergistic therapeutic agent in NSCLC therapy. Graphical Abstract: ga1